Symbolic interactionist takes on music - Schneider, Christopher J.; Kotarba, Joseph A. (Studies in symbolic interaction ;, 2016)
Participants from Couch-Stone Symposium 2014 have transformed their presentations into elegant papers for this collection. Chapters fall into three categorical themes, largely reflecting their position in the symposium but, more importantly, reflecting a natural progression in scope of symbolic interactionist work in music: moving from observations of the individual to observation of organizations to interdisciplinary observations of music from scholars in related disciplines.